Implementasi Sistem Informasi Sumber Daya Manusia Menggunakan Orangehrm - Studi Kasus di Salah Satu Toko Gadget Surabaya - Gugus Wijonarko; Alexander Wirapraja; Marcellino Imanuel Kurniawan (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2025)
Background - Human resources (HR) are a crucial and crucial element for a company because HR is the primary driver of operations and in achieving organizational goals. Effective HR management will improve productivity, performance, and a company's competitiveness in a competitive market. HR is an important company asset, especially in developing the company's business. Speed and accuracy in internal aspects, especially in employee management records, are currently irrelevant if done traditionally. Therefore, a company needs to utilize technology to increase competitiveness and strengthen the role of its human resources. Aim - This research aims to analyze as a utilize technology in the era of digital transformation that continues to develop and there is a shift from the role of HR to the role of technology, there is a strategic change and is oriented towards achieving overall organizational goals, namely a shift in the focus of human resource management from transactions to strategy. This helps human resource management professionals to focus more on more important things, such as the effectiveness of human resource planning, employee development, and strategic decision making that drive organizational success Design / methodology / approach - This study uses a research method model with a qualitative interpretative case study approach where this approach is used to implement OrangeHRM at gadget store X in Surabaya. Findings – The findings indicate that results of this study are where there is an application that can be used by employees to manage their personal data independently, through a module in the OrangeHRM application called Employee Self Service (ESS) for their company, they can also transfer routine operational tasks through this OrangeHRM application so that organizational management can focus on strategic planning to win the competition with competitors and improve aspects of organizational sustainability. Conclusion - OrangeHRM improves the efficiency of employees' daily work operations and is an application that allows them to independently manage their personal data. Through the Employee Self-Service (ESS) module within the OrangeHRM application, employees can also access their personal data management independently, thus helping the HR department improve the effectiveness and efficiency of employee data management. Research implication – This study contributes to future management studies, particularly in terms of efficiency, decision-making, and HR strategy development. The use of HRIS, including OrangeHRM, enables automation of HR tasks, improved data analysis, and data-driven decision-making, all of which contribute to increased management effectiveness. Limitations – This study has several limitations, include implementation costs, lack of flexibility, data security challenges, and internal resistance to change.